(untitled) (Journal of Training and Development, 2016)
This qualitative case study research was conducted to understand the perception of women in non-traditional occupations in Nepalese context. Seven participants from four nontraditional occupations, namely electrical, motorcycle mechanics (automobile), light vehicle driving and mechanical lathe operator were selected from Kathmandu valley. The data were collected using interview and focus group discussion. The findings revealed that involvement of Nepalese women in non-traditional occupations are very nominal. It is due to the conventional thinking towards women that they should do only the household chores. Non-traditional occupations for Nepalese women have not been women-friendly, however, they may if they do not feel inferior to male and avoid hesitation to work in these professions. The biggest challenge for women in these professions is the societal disbelief on the women’s work. They are behaved with suspicion by people and the society. Leg pulling and backbiting nature of people towards women in this profession are also the serious problems for them. Nevertheless, the female participants have got support from their family and organizations. Moreover, they have played significant roles from beginning to date to inspire them to continue their work.